Rational or irrational structure of the university structure to interactions in the learning economy and Transdisciplinarity (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2015)
The university as an organization that captures, processes, transmits and distributes information and knowledge must adapt to the new form of knowledge production. For that adaptation the university structure is requiring a comprehensive approach to analyze and reflect on linkages and feedback processes of learning with society and with networks of local actors. The university contribution to innovation process is a complex issue that transcends and put demands upon teachers, researchers related to third mission activities in order to go beyond a disciplinary thinking.
Keywords: University Structure Learning economy; Innovation Transdisciplinarity; Interaction model